ANALISIS VALUE STOCK DAN GROWTH STOCK DI BURSA EFEK INDONESIA SETELAH KRISIS GLOBAL 2008 Studi Kasus pada Perusahaan di Bursa Efek Indonesia periode 2002-2015 - Rabbani, Muhammad Fadhil; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2017)
This study was conducted to determine whether there are differences between the stock return of value stocks and growth stock in Indonesia before and after the world financial crisis that occurred in 2008. To investigate the difference, the stocks formed into a portfolio that is based on the 2002 calculated in 2002 and 2009 when the world financial crisis has ended. The formation of the portfolio based on stocks that have gone public before 2000 and have the complete data during the study period. For the determination of the categories of stocks used Price-to-Earnings ratio, price-to-book ratio and price-to-cash flow ratio. Shares of stock that has a very high ratio will be eliminate to avoid bias that may occur if the stocks are still included. Similarly, the stocks of which are negative because they do not meet the criteria as a value stock. Then ANOVA test conducted to determine differences in returns and Sharpe ratio on the portfolio which was formed in 2002 and in 2009. Results from this studies are not found differences in returns and Sharpe ratio on both the portfolio. This indicates that the formation of the portfolio by value stocks and growth stock can not be used as a guide to get a high return.